Proof : Photographs from Four Generations of a Texas Family - Williams, Byrd M. (Byrd Moore), IV, 1951- (Book collections on Project MUSE., 2016)
"The Byrd Williams Collection at the University of North Texas contains more than 10,000 prints and 300,000 negatives, accumulated by four generations of Texas photographers, all named Byrd Moore Williams. Beginning in the 1880s in Gainesville, the four Byrds photographed customers in their studios, urban landscapes, crime scenes, Pancho Villa's soldiers, televangelists, and whatever aroused their unpredictable and wide-ranging curiosity. When Byrd IV sat down to choose a selection from this dizzying array, he came face to face with the nature of mortality and memory, his own and his family's. In some cases these photos are the only evidence remaining that someone lived and breathed on this earth"--Amazon.